COMPARATIVE STUDY OF INTRAVENOUS PARACETAMOL AND TRAMADOL IN MANAGEMENT OF POST-OPERATIVE ANALGESIA IN PERCUTANEOUS NEPHROLITHOTOMY- RANDOMIZED CLINICAL STUDY - Dr Shanmuganantham S,Dr. Sachin,Dr Sahana G N,Dr Deepak P,Dr Jayashree V Nagaral,Dr Babitha L,Dr Mudavath Mohan Naik (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Postoperative pain is a critical aspect of surgical recovery, especially inprocedures like percutaneous nephrolithotomy (PCNL), where inadequate pain managementcan delay healing and increase complications. Common analgesics such as intravenous